Pemanfaatan Online Travel Agency (OTA) di Indonesia - Andy Mulyana; Ida ayu Made Er Meytha Gayatri; Wagini Wagini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this research is to find out the use of online travel agencies (OTA) in Indonesia. This article is based on a cross-sectional study because the target population of this study includes all Indonesian customers who use OTAs for travel bookings. Sampling through convenience sampling was used to select the sample because the customers are spread across the country, which makes it very difficult to communicate with each customer individually. The method for determining the number of research samples using SEM for data analysis is the number of items in the questionnaire multiplied by 10 cases. Since this study has four variables with six items for each variable, the maximum sample size that should be used is 24 x 10 = 240. Therefore, a sample size of 126 would be suitable for this study. Data collection was carried out using an online questionnaire. The analysis consisted of descriptive analysis and verification analysis using structural equation modeling (SEM) analysis using LISREL version 8.70 software. This analysis is used to calculate the utilization of online travel agencies (OTA) in Indonesia. The results of the statistical hypothesis, Service Quality has a positive but not significant effect on Customer Satisfaction. Brand image has a positive and significant effect on customer satisfaction. Service Quality has a positive and significant effect on Customer Loyalty. Brand image has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty